The Concept of Pawn (Rahn) from the Perspective of Mahmud Syaltut and Its Relevance to the Development of Islamic Economic Law Studies: A Literature Review - Husnawadi (Journal of Islamic Religious Studies, 2026)
This study examines the concept of pawn (rahn) from the perspective of Mahmud Syaltut and its relevance to the development of Islamic economic law studies. The research was motivated by the increasing importance of rahn within contemporary Islamic financial practices and the limited scholarly attention given to Mahmud Syaltut’s perspective on this issue. The study aimed to analyze comprehensively Syaltut’s views regarding rahn and to explore their contribution to contemporary Islamic economic law discourse. This research employed a qualitative approach using a literature review design. Data were collected from primary and secondary sources, including books, scientific journal articles, and relevant academic publications discussing rahn, fiqh muamalah, and Islamic economic law. The data were analyzed using descriptive and content analysis techniques to interpret systematically the conceptual framework of rahn according to Mahmud Syaltut. The findings reveal that Syaltut viewed rahn as a contract of trust and debt security rather than a profit-oriented investment mechanism. He emphasized that collateral should function solely as debt protection and should not become a means of economic exploitation. The study also found that Syaltut strongly rejected practices involving hidden riba, coercive consent, and unjust benefit-taking from pledged property. Furthermore, his perspective highlights the ethical dimensions of Islamic economic law, including justice, transparency, and social responsibility. This study concludes that Mahmud Syaltut’s thought remains highly relevant to the contemporary development of Islamic financial systems and contributes significantly to strengthening the ethical foundation of Islamic economic law studies.